Adaptive Reuse of Pos Bloc and M Bloc: The Intersection of Third Place, Nostalgia, and Circular Economy - Fajarwati, Ade Ariyani Sari (Bina Nusantara University, 2023)
The research examined the adaptive reuse strategy of heritage buildings that hold nostalgic value as commercial spaces with the third-place concept approach. The need for space facilities for urban communities continued to change based on the activities of its users. People of productive age living in big cities and the suburbs needed space for gathering and relaxation between work and homes. On the other hand, in the downtown area, several heritage buildings were still sturdy and owned by the state but were no longer used optimally or maintained. Adaptive reuse of heritage buildings was a strategy that emerged as a solution to address this need. Nostalgia contained in the preservation of cultural heritage buildings was a significant value to attract visitors and impact economic benefits. Studies were needed regarding aligning economic values with social and environmental needs in adaptive reuse. Qualitative methods with in-depth observations were carried out at two sites, namely the adaptive reuse of Pos Bloc and M Bloc Jakarta, heritage buildings gathering spaces for workers and young people of productive age. This method was applied to analyze the history of the building, the current condition of the interior, and the impact on the economy and community. The research finds that the adaptive reuse of Pos Bloc and M Bloc as third spaces by utilizing nostalgic values is a strategy to maintain cultural heritage as well as an effort to drive a circular economy.